Variations of Individualism and Collectivism Within Individuals: The Effects of Value Orientations Towards Family, Friends and Work - Nguyen, Huu An (H. : ĐHQGHN, 2019)
Individualism-Collectivism is a commonly used dimension in comparative cultural studies. The performance of individualism and collectivism has been found diverse at different levels of analysis. While the constructs are seen as opposite poles of a bipolar dimension at the national level, they are demonstrated as independent concepts at the individual level. Recent debates have suggested these constructs should be treated as individual states in relation to social contexts rather than individual traits at the individual level of analysis. This perspective allows us to explain possibilities for any individual to have both individualistic and collectivistic attitudes. Based on the data of three latest waves of World Values Survey, this paper tests the variations of individualism and collectivism at the individual level under effects of value orientations toward key social relations that individuals involved in, namely family, friends and work. Furthermore, the differences in the effects between the “West” and the “East” and how it changes over time are also taken into account. The findings show that individualism is emphasized among individuals who place work as important, which is stronger in the “West” than in the “East” but not clear over time. Collectivism is favored among individuals who consider family and friends significant, and these links are found stronger in the “East” than in the “West”. Especially, individuals‟ preference for the value towards family has negative effects on individualism but positive impact on collectivism and these links are evident over the three waves.